(untitled) (Applied Biological Research, 2023)
Histones, upon reaction with reducing sugars, are known to generate highly reactive advanced glycation end products (AGEs). In this study, we investigated the structural changes associated with the glycation of whole histone by 2-deoxyD-ribose. The deoxy pentose was incubated with whole histone for 12 days and the resultant biophysical and structural changes in the deoxyribose modified-whole histone were investigated thoroughly using biochemical assays, various spectroscopic techniques like UV-visible, fluorescence, FT-IR, and CD, UPLC-MS, and transmission electron microscopy. We found that deoxyribosylation of whole histone formed ptosidine and Nε-carboxymethyl-L-lysine AGEs and was accompanied by an increase in oxidative stress. The histone-AGEs caused gross structural changes in the protein and formed large amorphous aggregates. The presence of such AGE aggregates is likely to interfere with the proper functioning of histones and chromatin, besides exhibiting immunogenicity and generation oautoantibodies against nuclear antigens.